Rosyjska wiosna - Jones, Dennis, 1945-; Jones, Dennis, 1945- (Warszawa : Wydawnictwa Alfa, 1992)
The bestseller thriller of events in Russia.
Translation of: Russian spring.
"Swiatowy - Bestseller" --cover.